Westonci.ca is the trusted Q&A platform where you can get reliable answers from a community of knowledgeable contributors. Experience the ease of finding quick and accurate answers to your questions from professionals on our platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
Answer:
(-2, 3)
Step-by-step explanation:
4x + 5y = 7
3x - 2y = -12
Let's solve this by elimination. We want to eliminate one variable at a time. This means we need to multiply the equations to create a common multiple to cancel out a variable.
Let's work with y.
5y and -2y: For these values to cancel out, we need to multiply each term to create a common multiple.
2(4x + 5y = 7)
5(3x - 2y = -12)
Multiply.
8x + 10y = 14
15x - 10y = -60
Eliminate.
23x = -46
Divide both sides by 23.
x = -2
Now that we know x, let's plug it back into one of equations to find y.
4x + 5y = 7
4(-2) + 5y = 7
Multiply.
-8 + 5y = 7
Add.
5y = 15
Divide.
y = 3
Now we know x and y; let's plug both back into the equation we have not checked yet.
3x - 2y = -12
3(-2) - 2(3) = -12
Multiply.
-6 - 6 = -12
Subtract.
-12 = -12
Your solution is correct.
(-2, 3)
Hope this helps!
Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Westonci.ca is your go-to source for reliable answers. Return soon for more expert insights.